2005
DOI: 10.1590/s0034-89102005000100016
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculose em Salvador: custos para o sistema de saúde e para as famílias

Abstract: ObjectiveTuberculosis is one the greatest causes of mortality worldwide, but its economic effects are not well known. This study had the objective of estimating the costs to the public and private healthcare systems and to families of tuberculosis treatment and prevention. Methods This study was made in the municipality of Salvador, State of Bahia, Brazil, in 1999. Data for estimating the costs to the healthcare system were collected from the Department of Health, healthcare facilities and a philanthropic inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
11

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 6 publications
0
12
0
11
Order By: Relevance
“…This illustrates the social cost of TB and the impact of such cases on the budget of the TB control program, since it is estimated that the cost of hospital treatment is 14 times higher than that of outpatient treatment. (20) It has been demonstrated that 65% of the TB control program budget is expended for hospitalizations, and that the families of patients allocate 33% of their income to expenses related to the maintenance of the patients during hospital treatment. (20) The high proportion of hospitalizations can be partly explained by the low adherence to treatment, which increases the risk of developing severe forms of the disease, (14,15) or by the high prevalence of patients with TB/ HIV coinfection, (18) as well as by the fact that TB is a hyperendemic disease in the community studied, creating conditions for a more marked only the intrinsic limitations of the surveillance but also underreporting, the lack of complete information and the difficulties that arise from working with multiple data sources, as well as the fact that only cases of PTB were analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…This illustrates the social cost of TB and the impact of such cases on the budget of the TB control program, since it is estimated that the cost of hospital treatment is 14 times higher than that of outpatient treatment. (20) It has been demonstrated that 65% of the TB control program budget is expended for hospitalizations, and that the families of patients allocate 33% of their income to expenses related to the maintenance of the patients during hospital treatment. (20) The high proportion of hospitalizations can be partly explained by the low adherence to treatment, which increases the risk of developing severe forms of the disease, (14,15) or by the high prevalence of patients with TB/ HIV coinfection, (18) as well as by the fact that TB is a hyperendemic disease in the community studied, creating conditions for a more marked only the intrinsic limitations of the surveillance but also underreporting, the lack of complete information and the difficulties that arise from working with multiple data sources, as well as the fact that only cases of PTB were analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…In a county in northeastern Brazil the cost of treatment of each new case was approximately US$ 103, but 27 times higher for treatment of multidrugresistant tuberculosis. The disease incurs expenses of approximately 33% of the patient's family income; and of the public health care services' expenditure on tuberculosis, up to 65% is required for hospitalizations and 32% for treatment, with only 3% being left for prevention (47). These costs have been estimated to be enough to fund R&D of a new drug for tuberculosis (26).…”
Section: Discussionmentioning
confidence: 99%
“…Além disso, os gastos com essa doença também oneram os orçamentos familiares, que pode estar relacionado diretamente ao tratamento e principalmente à perda de renda por conta da doença e internação. 6 As internações por TB também demonstram ser dispendiosas para os cofres públicos principalmente por se tratarem em geral de casos graves que envolvem comorbidades e complicações -tratamentos específicos e mais caros -e caracterizam-se por uma menor taxa de cura, maior tempo de internação e grande número de evolução para óbito. 7 Para a realização de tal estudo, foram utilizados dados secundários do SIH/SUS, o que pode gerar limitações, seja pela qualidade destes ou por agregar somente atendimentos do sistema público de saúde do Brasil.…”
Section: Resultsunclassified
“…Essa variável é apresentada neste estudo e mostra-se semelhante a outras publicações. 6,11,12 Há possibilidade de que a maior produtividade e o menor acesso de homens aos serviços de saúde sejam um fator determinante para a infecção. 13,14 Em relação à raça/cor ficou evidenciada a limitação do presente estudo em consequência do subregistro para esta variável.…”
Section: Discussionunclassified
See 1 more Smart Citation